Mitigating the Impact of Inflation, But How? - ZG Überblick (Wirtschaftsdienst)
Abstract The inflation rate has been at a high level for several months. Consumer prices in Germany increased by 7,5 % in July 2022 compared to the previous year. The associated loss of purchasing power is causing problems and uncertainty among citizens. It can be observed that especially people at risk of poverty who are dependent on transfers suffer from this. In addition, especially low income groups suffer from inflation, as they spend a high proportion of their income on food and energy. In a first step, politicians have prepared a relief package that includes, among other things, the petrol rebate and the 9-Euro-Ticket. Especially at the lower end of the income distribution, inflation is nevertheless causing distortions that justify the question of whether further measures are necessary.